Abdominal pain with intra-adrenal bleeding as an initial presentation of pheochromocytoma. Issue 1 (11th January 2021) - Lambrecht, Astrid; Inglis, Joshua M; Young, Robert
Abstract : A 55-year-old man presented with severe right upper quadrant abdominal pain and hypertension up to 231/171 mm Hg on a background of a known adrenal mass, intravenous drug use and recurrent anxiety attacks. CT showed heterogenous lesion of the right adrenal gland but the sudden severe pain remained unexplained. After correction of the blood pressure with analgesia and antihypertensives, the patient developed a type 2 non-ST-elevation myocardial infarction that was treated with aspirin and therapeutic enoxaparin. This resulted in worsening pain and a repeat CT angiogram showed a haemoretroperitoneum around the right adrenal lesion. On review, an occult intra-adrenal haemorrhage was identified on the initial CT scan. Presumably this concealed haemorrhage caused the initial pain crisis and later decompressed into the retroperitoneal space. Raised metanephrine levels confirmed the diagnosis of pheochromocytoma and after preoperative optimisation with phenoxybenzamine, an open right adrenalectomy was performed.